Clinical factors associated with trunk control after stroke: A prospective study. Issue 3 (3rd April 2021) - Martins, Laís Geronutti; Molle da Costa, Rafael Dalle; Alvarez Sartor, Lorena Cristina; Thomaz de Souza, Juli; Winckler, Fernanda Cristina; Regina da Silva, Taís; Modolo, Gabriel Pinheiro; Nunes, Hélio Rubens De Carvalho; Bazan, Silméia Garcia Zanati; Martin, Luis Cuadrado; Luvizutto, Gustavo José; Bazan, Rodrigo
ABSTRACT: Introduction: Poor trunk control after stroke can impact recovery of global functional abilities. Therefore, the aim of this study was to evaluate whether clinical and functional data from stroke participants can be used to predict trunk control at 90 days. Methods: This is a prospective study of 37 participants with stroke. The variables evaluated at hospital discharge were stroke severity (National Institute of Health Stroke Scale - NIHSS); functional capacity (modified Rankin scale - mRS); handgrip; and cognitive function. At 90 days, the variables evaluated were autonomy (Functional Independence Measure – FIM, Barthel Index); gait mobility (Tinetti mobility test -TMT); quality of life (European Quality of Life Scale - EuroQol-5D) and trunk control (trunk impairment scale - TIS). The participants were considered to have satisfactory (TIS³14) or non-satisfactory trunk control (TIS≤13), and the differences between them were assessed by chi-square test (categorical variables) and Mann-Whitney/unpaired t-test (continuous variables). A ROC curve was used to show cut-off value of clinical variables to predict trunk control. Results: The unsatisfactory trunk control group presented ahigher NIHSS at discharge (p=0.01), higher mRS at discharge (p=0.00), lower Barthel Index at 90 days (p=0.03), lower FIM at 90 days (p=0.01) and lower TMT at 90 days (p=0.00) than the satisfactory trunk control group. The best cut-off points for the NIHSS and mRS scores at discharge for predicting unsatisfactory trunk control are ≥6 and ≥3, respectively. Conclusion: Greater NIHSS and mRS scores at hospital discharge increase the chance of unsatisfactory trunk control at 90 days after stroke.